Towards Distributed BPEL Orchestrations - Baresi, Luciano; Maurino, Andrea; Modafferi, Stefano (Electronic Communications of the EASST, 2007)
Web services are imposing as the technology to integrate highly heterogeneoussystems. BPEL, the standard technology to compose services, assumes asingle âorchestratorâ that controls the execution flow and coordinates the interactionswith selected services. This centralized approach simplifies the coordinationamong components, but it is also a too heavy constraint. To this end, the paperintroduces the idea of distributed orchestrations and presents a proposal to coupleBPEL and distributed execution in mobile settings. The approach âexemplifiedon a simple case studyâ transforms a centralized BPEL process into a set of coordinatedprocesses. An explicit meta-model and graph transformation supply theformal grounding to obtain a set of related processes, and to add the communicationinfrastructure among the newly created processes. The paper also presents a communicationinfrastructure based on tuple spaces to make the different orchestratorsinteract in mobile contexts.Keywords: WS-BPEL, Graph